PENGETAHUAN TENTANG REGULASI EMOSI ORANGTUA DALAM PANDEMI COVID-19 - Lunanta, Lita Patricia (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Children reflect on their parents. Children can absorb their parents’ emotions and copy their parents’ behaviors. This seminar was held to raise awareness of the possibility for parents to have anxieties and emotional problems that they didn’t realize. This sharing of materials about emotion regulation aimed to make parents realize their emotional state, especially in the pandemic of Covid-19. Furthermore, it aimed to build understanding about the concept of emotion regulations and to master the strategies to be used in regulating emotions. This venue was held in scientific forum for lecturer and staffs of Esa Unggul University using online meeting with Zoom and Facebook live application programmes. This seminar began with explanation of the materials and continued with discussion (questions and answers) to enhanced understanding. From the survey, it was also found that most of them already applied regulation emotion strategy in facing their anxieties. From the pooling, it was found that most of the participants felt that the seminar is very interesting (58.8%), very good (47%), felt that it went accordingly with their hope (67%), the materials were well received (47%), and all of them (100%) would join similar seminar.  Keywords: emotion regulation, anxiety, covid-19